Salvia adiyamanensis (Lamiaceae), a new species from South East Anatolia, Turkey - İlçi̇m, Ahmet; Tel, Ahmet Zafer; Kocabaş, Yusuf Ziya (Phytotaxa, 2023)
In this study, the new species Salvia adiyamanensis İlçim & Tel (Lamiaceae) is described from Adiyaman province, Turkey. The relevant diagnostic characters with respect to the species were presented. In addition, we presented the notes concerned with the ecology, habitat, conservation status, pollen and seed morphology of the species. We furthermore constructed a distribution map for the new species and other related species.